Do current maternal health staffing and bed occupancy benchmarks work in practice? Results from a simulation model - Giorgia Gon; Carolin Vegvari; Rebecca F Baggaley; Said Mohammed Ali; Salma Abdi Mahmoud; Farhat Jowhar (BMJ Public Health)
Introduction The WHO has issued the global target of reducing maternal mortality rates by two-thirds of 2010 baseline levels by 2030. In low-income settings, high birth rates and a relative lack of medical resources mean that an efficient use of resources and skilled staff is important in ensuring quality of intrapartum and postpartum care.Methods We use a stochastic, individual-based model to explore whether WHO resourcing benchmarks are sufficient to ensure consistent quality of care. We simulate all deliveries occurring in a region over a year, with date and time of presentation of each woman delivering at a facility assigned at random. Each woman stays in the delivery room for an assigned duration before her delivery, then moves to the maternity ward, followed by discharge. We explore the potential impact of seasonality of births on our findings and then apply the model to a real-world setting using 2014 data from Emergency Obstetric Care (EmOC) facilities in Zanzibar, United Republic of Tanzania.Results We find that small EmOCs are frequently empty, while larger EmOCs are at risk of temporarily falling below minimum recommended staff-to-patient ratios. Similarly for Zanzibar, capacity of EmOCs in terms of beds is rarely exceeded. Where over-capacity occurs, it is generally smaller, basic EmOCs (BEmOCs) that are affected. In contrast, capacity in terms of staffing (skilled birth attendants:women in labour ratio) is exceeded almost 50% of the time in larger Comprehensive EmOCs (CEmOCs).Conclusions Our findings suggest that increasing staffing levels of CEmOCs while maintaining fewer small BEmOCs may improve quality of care (by increasing the staff-to-patient ratio for the most frequently used facilities), provided that timely access to EmOCs for all women can still be guaranteed. Alternatively, BEmOCs may need to be upgraded to ensure that women trust and choose these facilities for giving birth, thus relieving pressure on CEmOCs.